Integrated photoelectrocatalytic reduction and oxidation processes to achieve efficient degradation of fluoxetine in pharmaceutical wastewater - Yanpeng Liu; Zixiao Zhu; Miao Ren; Jingyi Fu; Bo Yang; Xu Zhao (Journal of Environmental Sciences, 2026)

Highland barley polysaccharides promoted lactose intestinal fermentation in vitro: Unveiling the dynamic response of gut microbiota and polysaccharide structure - Jingyi Wang; Jiaxin Wei; Yuxuan Fu; Qinfei Wan; Jiayi Zhou; Kai Hu; Zisheng Han (Food Research International, 2026)

Optimization of microencapsulation process for the fabrication of methyleugenol microcapsules and investigation of their antifungal effects on Fusarium avenaceum - Jingyi Tang; Haibin Liao; Xueqin Fu; Yonghong Xie; Zhengrong Zou; Zaizhi Liu (Food Chemistry, 2026)

Fabrication of a flower-like MgIn2S4/BiOBr Z-scheme heterostructure via an in situ route for organic pollutant photodegradation - Jingyi Li; Huanli Wang; Jingchuan Fu; Chenyu Zhu; Ting Liu; Wei Xu; Huawei Zhang (Journal of Cleaner Production, 2026)

Synergistic effects of spent mushroom substrate and biochar on enhanced humification and heavy metal passivation during rapeseed straw composting - Jinfeng He; Jingyi Fu; Shanshuai Chen; Xiaoyong Liao; Huaqin Xu; Muhammad Usman Khan; Weiwei Huang (Applied Soil Ecology, 2026)

The mechanistic nexus between microplastics and chronic liver disease: A review of current evidence - Shiyun Pu; Changyu Ren; Jiao Liu; Jingyi Zhang; Yan Wang; Ke Fu; Tong Wu (Chemico-Biological Interactions, 2026)

Operational monitoring windows from cumulative rainfall to chlorophyll-a in subtropical reservoirs - Jingxin Wei; Peiliang Chen; Xingcheng Fu; Jie Ling; Bingqing Xiao; Xuedong Xie; Bozhu Huang; Jingyi Cen; Songhui Lu (Environmental Monitoring and Assessment, 2026)

Aridity and grazing regulate the effects of grassland biodiversity on the trade-offs and synergies among ecosystem functions in drylands - Weiling Niu; Jingyi Ding; Wenwu Zhao; Jing Wang; Wenzhu Tu; Yue Liu; Bojie Fu (Agriculture, Ecosystems & Environment, 2026)

Positive effects of highland barley β-glucan intervention on lactose fermentation efficiency and metabolites: unveiling the responses of the gut microbiota through an in vitro fermentation model - Jingyi Wang; Yuxuan Fu; Jiaxin Wei; Jun Yang; Kai Hu; Mengzhou Zhou; Mingye Peng (Food Research International, 2026)

Construction of a novel S-scheme Bi4Ti3O12/MgIn2S4 heterojunction for efficient photocatalytic removal of tetracycline and Cr(VI) - Jingchuan Fu; Jiayuan Liu; Jingyi Li; Chenyu Zhu; Huanli Wang (Environmental Research, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Spatial source apportionment of n-alkanes and their effects on carbon pool dynamics and microbial communities in a river–estuary–offshore continuum - Jingyi Xu; Qiang Fu; Kaichao Wan; Fujun Shi; Weidong Wang (Water Research, 2026)

Exposure to titanium and nickel as the novel risk factors for PCOS: Evidence from a case control study in Xiamen, China - Zhineng Fu; Lanlan Liu; Jingyi Wang; Fengkai Ruan; Yurong Chen; Liying Zhou; Chunyan Yang; Jiali Cai; Runzeng Liu; Chengyong He; Xiaoming Jiang; Zhenghong Zuo (Journal of Environmental Sciences, 2026)

A closed-cycle and low-cost strategy for recovery and reuse of toxic lead from discarded perovskite photocatalysts - Jingyi Hou; Yuanyuan Zhang; Yuanfeng Luo; Qiao Chen; Jiaxing Feng; Yuan Zhang; Ranran Fu; Linxing Shi (Journal of Hazardous Materials, 2025)

An innovative dual-driven strategy to accelerate and strengthen TGase-induced pea protein gelation via static magnetic field and arabinoxylan pretreatments - Zuwei Yu; Yuxuan Fu; Jiaxin Wei; Ting Yang; Kai Hu; Jingyi Wang (Innovative Food Science & Emerging Technologies, 2025)

Aquatic acidification amplified ibuprofen toxicity in Chlorella vulgaris: Integrating oxidative stress markers and metabolomic profiles - Jing Fu; Qichen Yuan; Xin Hu; Jingyi Li; Liang Tang (Environmental Research, 2025)

Interfacial water layer modulation for efficient photocatalytic CO2 reduction - Jingyi Pang; Hang Zhou; Zejiang Huang; Xiaomeng You; Beibei Xu; Xiaobin Fu; Yilong Weng; Xue-Lu Wang; Ye-Feng Yao (Chemical Engineering Journal, 2025)

Moss dominated biological soil crust reduced runoff by increasing wetted perimeter of cross-section - Kangmin Gu; Yunge Zhao; Junyu Zhang; Jingrong Song; Liqian Gao; Jingyi Ji; Liqiao Fu (CATENA, 2025)

Identification of a missing Pictet–Spenglerase in the Gloriosa superba L. colchicine biosynthesis pathway - Jingyi Sun; Huapeng Sun; Zhiqiang Xiong; Xuefei Jiang; Xiaona Fu; Hanqing Cong; Fei Qiao (Molecular Biology Reports, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

Highly selective reduction of CO2 to CH4 mediated by 2D/0D Cs3Bi2Br9/BiOBr heterojunctions with atomic-level intimate interfaces - Tingting Ren; Yanqing Zhang; Suning Fu; Yuanming Hou; Jiaxin Wang; Jingyi Qin; Zhengzheng Xie; Jianjun Yang; Zhongjie Guan; Shilong Jiao; Qiuye Li; Xianwei Fu (Chemical Engineering Journal, 2025)

Delivery of penetration-enhancing antioxidant polyphenol nanoparticles with Codonopsis pilosula polysaccharide microneedles for synergistic treatment of psoriasis - Siqi Liu; Silu Song; Yu Zhang; Liming Yan; Yuhui Chen; Wanrong Li; Banaz Jalil; Chun Wu; Yuping Fu; Xingfu Chen; Jingyi Gu; Lixia Li; et al. (Carbohydrate Polymers, 2025)

The role of biocrusts in complicating runoff pathways and redistributing water resources in drylands - Jingyi Ji; Yunge Zhao; Wantao Zhang; Xinyi Shen; Yun Fu; Kangmin Gu (Journal of Hydrology, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Screening of monascus SPP. and regulation effects of quorum sensing molecules and co-factors based on tocopherol high-accumulation - Jingyi Fu; Qifeng Wu; Liu Tang; Yixiang Zhang; Shiji Sun; Yu Zheng; Anyan Wu; Likang Qin; Haiying Zeng (Food Bioscience, 2025)

Eco-friendly chitosan-based composite film with anti-dissolution capacity as active packaging for fruit preservation - Jingyi Zhao; Huijie Yang; Chao Li; Zhihang Xu; Peng Shan; Chenglong Fu; Yehan Tao; Jinwen Hu; Haisong Wang; Jian Du (Food Hydrocolloids, 2025)

Single-atom Ru confined in self-supported mesoporous carbon films for efficient and stable acidic oxygen evolution - Tianhao Liu; Jingyi Guo; Aiping Wu; Di Shen; Yuying Fan; Yu Fu; Zhijian Liang; Dongxu Wang; Ying Xie; Chungui Tian (Chemical Engineering Journal, 2025)

Fatigue Reliability Analysis of Offshore Wind Turbines Under Combined Wind–Wave Excitation via Direct Probability Integral Method - Jingyi Ding; Hanshu Chen; Xiaoting Liu; Youssef F. Rashed; Zhuojia Fu (Journal of Marine Science and Engineering, 2025)
As offshore wind turbines develop into deepwater operations, accurately quantifying the impact of stochastic excitation in complex sea environments on offshore wind turbines and conducting structural fatigue reliability analysis has become challenging. In this paper, based on long-term wind–wave reanalysis data from the South China Sea, a novel direct probability integral method (DPIM) is developed for the stochastic response and fatigue reliability analysis of the key components for the floating offshore wind turbine structures, under combined wind–wave excitation. A 5 MW floating offshore wind turbine is considered as the research object, and a comprehensive analysis of the wind turbine system is performed to assess the short-term fatigue damage at the tower base and blade root. The proposed method’s accuracy and efficiency are validated by comparing the results to those obtained from Monte Carlo simulations (MCS) and a subset simulation (SSM). Additionally, a sensitivity analysis is conducted to evaluate the impact of different environmental parameters on fatigue damage, providing valuable insights for the design and operation of FOWTs in varying sea conditions. Furthermore, the results indicate that the fatigue life of floating offshore wind turbine (FOWT) structures under combined wind–wave excitation meets the design requirements. Notably, the fatigue reliability of the wind turbine under aligned wind–wave conditions is lower compared to misaligned wind–wave conditions.

A multi-omic single-cell landscape of the aging mouse ovary - Jian Zhang; Shunze Jia; Zehua Zheng; Lanrui Cao; Jingyi Zhou; Xudong Fu (GeroScience, 2025)

Global effects of livestock grazing on ecosystem functions vary with grazing management and environment - Weiling Niu; Jingyi Ding; Bojie Fu; Wenwu Zhao; David Eldridge (Agriculture, Ecosystems & Environment, 2025)

Effect of wall slip of CO2-in-water foams on enhanced oil recovery - Biao Xu; Jiuqing Li; Lin Zhu; Junyan Xu; Runze Wang; Shun Li; Jiajia Fu; Jingyi Yang; Tao Liu (Chemical Engineering Journal, 2025)

A novel inactivated oral rabies vaccine with the incorporation of U-OMP19 enhances the immunogenicity by reducing viral proteins degradation and activating dendritic cells in a mouse model - Zonghui Zeng; Di Wu; Jingyi Xiong; Jianqing Zhao; Chuan Liang; Qiong Wu; Chengli Huang; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Metabolic profile changes of zebrafish larvae in the single- and co-exposures of microplastics and phenanthrene - Jingyi Li; Xiao Liu; Jing Fu; Zhiyuan Gong; Sabrina Yanan Jiang; J. Paul Chen (Science of The Total Environment, 2024)

Degradation of thiosulfate ions in sodium aluminate solution photocatalyzed by Co-TiO2@ZIF-8 - Jingyi Hao; Binchuan Li; Jing Dai; Daxue Fu; Yongfeng Chang; Jianshe Chen; Na Xu; Kuiren Liu; Qing Han (Minerals Engineering, 2024)

Synthesis of a novel flower-like Bi4Ti3O12/AgI Z-type heterojunction for efficient photocatalytic removal of tetracycline antibiotic and RhB - Jiayuan Liu; Yuanfei Li; Xiaodong Liu; Jingchuan Fu; Jingyi Li; Yuchen Liu; Huanli Wang; Shijie Li (Journal of Water Process Engineering, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Ecosystem multifunctionality is more related to the indirect effects than to the direct effects of human management in China's drylands - Weiling Niu; Jingyi Ding; Bojie Fu; Wenwu Zhao; Yi Han; Ao Zhou; Yue Liu; David Eldridge (Journal of Environmental Management, 2024)

Towards promoting wound healing: A near-infrared light-triggered persistently antibacterial, synergistically hemostatic nanoarchitecture-integrated chitosan hydrogel - Zhao-Xi Zhou; Jingyi Li; Jianfeng Hu; Heqing Fu (Carbohydrate Polymers, 2024)

Cholesterol depletion inhibits rabies virus infection by restricting viral adsorption and fusion - Qingxiu Hou; Caiqian Wang; Jingyi Xiong; Haoran Wang; Zhihui Wang; Juanjuan Zhao; Qiong Wu; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Exploring the interference mechanisms of surface and aqueous complexes with groundwater arsenate and arsenite adsorption - Shan Hu; Jingyi Fu; Shenmin Zhou (Environmental Science and Pollution Research, 2024)

Effect of common low-molecular-weight organic acid on the photodegradation of sertraline by ferrihydrite - Ziyan Zhou; Dingding Wu; Hao Wu; Boming Fu; Xinhao Wang; Jingyi Ling; Xin Jin; Cheng Gu (Chemosphere, 2023)

A critical review on separation and extraction of scandium from industrial wastes: Methods, difficulties, and mechanism - Jingyi Chi; Cuizhen Wang; Guangzhu Zhou; Xiaoning Fu; Xi Chen; Xueying Yin; Zijin Zhang; Yuanhao Wang (Journal of Environmental Chemical Engineering, 2023)

A novel narnavirus isolated from Colletotrichum curcumae strain 780-2T - Yujia Fu; Tian Wang; Siyu Zhou; Jingyi Zhou; Yang Zhao; Daipeng Chen; Li Zheng (Archives of Virology, 2023)

Effect of aeration/micro-aeration on lignocellulosic decomposition, maturity and seedling phytotoxicity during full-scale biogas residues composting - Xingyao Meng; Qingping Wang; Xixi Zhao; Yafan Cai; Jingyi Fu; Mingcheng Zhu; Xuguang Ma; Pan Wang; Rufei Liu; Yongjing Wang; Wei Liu; Lianhai Ren (Waste Management, 2023)

Numerical investigation of suppressing thermal runaway propagation in a lithium-ion battery pack using thermal insulators - Junhui Gong; Bo Liu; Haochen Lian; Jingyi Liu; Hui Fu; Yuxuan Miao; Jialong Liu (Process Safety and Environmental Protection, 2023)

The role of climate literacy in individual response to climate change: evidence from China - Wu-Lin Pan; Ruguo Fan; Wei Pan; Xinyu Ma; Cheng Hu; Piao Fu; Jingyi Su (Journal of Cleaner Production, 2023)

Progress in semiconductor materials for photocathodic protection: Design strategies and applications in marine corrosion protection - Xi Chen; Guangzhu Zhou; Xiutong Wang; Hui Xu; Cuizhen Wang; Qiuhui Yao; Jingyi Chi; Xiaoning Fu; Yuanhao Wang; Xueying Yin; Zijin Zhang (Chemosphere, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Characterization of a novel mycotombus-like virus from the plant-pathogenic fungus Phoma matteucciicola - Siyu Zhou; Daipeng Chen; Yujia Fu; Jingyi Zhou; Yingqing Yang; Changping Xie; Li Zheng (Archives of Virology, 2023)

Effects of stand age and structure on root distribution and root water uptake in fast-growing poplar plantations - Wei Zhu; Ou Zhou; Yiming Sun; Ximeng Li; Nan Di; Doudou Li; Gulimire Yilihamu; Yafei Wang; Jingyi Fu; Benye Xi; Liming Jia (Journal of Hydrology, 2023)

Insight into photo-fenton catalytic degradation of tetracycline by environmental friendly nanocomposite 1T-2H hybrid phases MoS2/Fe3O4/g-C3N4 - Rongchao Yang; Guangzhu Zhou; Cuizhen Wang; Yin Liu; Yanyun Zhao; Yinming Li; Xiaoning Fu; Jingyi Chi; Xi Chen; Hui Fang; Zheng Qin (Journal of Cleaner Production, 2023)

Supercooled sugar alcohols stabilized by alkali hydroxides for long-term room-temperature phase change solar-thermal energy storage - Xiaoxiang Li; Jingyi Zhang; Yizhe Liu; Yangzhe Xu; Kehang Cui; Zhenpeng Yao; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Climate Warming Mitigation from Nationally Determined Contributions - Bo Fu; Jingyi Li; Thomas Gasser; Philippe Ciais; Shilong Piao; Shu Tao; Guofeng Shen; Yuqin Lai; Luchao Han; Bengang Li (Advances in Atmospheric Sciences, 2022)

NTA-assisted mineral element and lead transportation in Eremochloa ophiuroides (Munro) Hack - Siyi Pu; Xinyi Cai; Wenjuan Wang; Xingke Liu; Shangguan Li; Jingyi Fu; Lingxia Sun; Jun Ma; Mingyan Jiang; Xi Li (Environmental Science and Pollution Research, 2022)

Melatonin-assisted phytoremediation of Pb-contaminated soil using bermudagrass - Chengcheng Xie; Siyi Pu; Xi Xiong; Shuyu Chen; Lingli Peng; Jingyi Fu; Lingxia Sun; Baimeng Guo; Mingyan Jiang; Xi Li (Environmental Science and Pollution Research, 2021)

The first complete genome sequence of an iflavirus from the endoparasitoid wasp Tetrastichus brontispae - E Meng; Baozhen Tang; Jingyi Li; Lang Fu; Youming Hou (Archives of Virology, 2021)

Discovery of 3-(thiophen/thiazole-2-ylthio)pyridine derivatives as multitarget anticancer agents - Jiankang Zhang; Jianjun Xi; Ruoyu He; Rangxiao Zhuang; Limin Kong; Liping Fu; Yanmei Zhao; Chong Zhang; Linghui Zeng; Jingyi Lu; Rujia Tao; Zhengmengtong Liu; et al. (Medicinal Chemistry Research, 2019)

Differentiation of the Agonists and Antagonists of the α7 Nicotinic Acetylcholine Receptor - Guanzhao Wu; Qingliang Xu; Yilei Bao; Yuwei Liu; Qian Li; Zhengyu Fang; Jingyi Fu; Yuhang Ding; Zhiqing Liang; Tao Jiang; Rilei Yu (Journal of Ocean University of China, 2019)

Changes of non-protein thiols in root and organic acids in xylem sap involved in cadmium translocation of cadmium-safe rice line (Oryza Sative L.) - Qin Li; Jingyi Guo; Xizhou Zhang; Haiying Yu; Fu Huang; Lu Zhang; Man Zhang; Tingxuan Li (Plant and Soil, 2019)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Pollution assessment of heavy metals along the Mekong River and dam effects - Kaidao Fu; Bin Su; Daming He; Xixi Lu; Jingyi Song; Jiangcheng Huang (Journal of Geographical Sciences, 2012)

Carboxylate-Terminated Double-Hydrophilic Block Copolymer as an Effective and Environmentally Friendly Inhibitor for Carbonate and Sulfate Scales in Cooling Water Systems - Guangqing Liu; Yuming Zhou; Jingyi Huang; Qingzhao Yao; Lei Ling; Peixin Zhang; Xiaofeng Zhong; Change Fu; Wendao Wu; Wei Sun; Zhengjun Hu (Water, Air, & Soil Pollution, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)